Penanaman Pohon Produksi Untuk Meningkatkan Produktivitas Lahan Pada Kebun Bibit Rakyat di Kabupaten Karo - Pulungan, Abraham Ismail; Sitepu, Dermawanta; Damanik, Kristo; Depari, Nelfita Rizka S.; Siregar, Rahmad Syukur; Suranto, Suranto (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2025)
The People's Seed Garden (KBR) is a government program to provide multipurpose forest plant seedlings (MPTS) which are carried out independently by community forest farmer groups in rural areas. The background of the KBR development activity is as an effort to plant on critical land or empty land and unproductive forest land inside and outside forest areas. One of the efforts to restore the condition of the critical River Basin Area (DAS), this effort also provides results in the form of wood, sap, fruit, leaves, flowers, fiber, animal feed, and so on. In order to restore, maintain and improve the function of forests and land and improve community welfare, BPDAS-WU Sei Wampu Ular carries out the Development of the People's Seed Garden with the aim of supporting the greening and nature conservation program to improve welfare through efforts to maintain plants that are productive in a relatively short time.